Análisis de los factores que incidieron en el incumplimiento de las obligaciones tributarias en el Cantón Bolívar durante el año 2014. - Lucas Zamora, Estalin Onofre (2016)
Tax noncompliance is one of the main phenomena affecting tax collection because it produces insufficient resources required to ensure the sustainability of quality public services, the study aimed to analyze the factors affecting failure tax obligations in the canton Bolivar during 2014, having as main objectives, identification of taxpayers who failed to comply with tax obligations, determining the factors that led to this hierarchizing default based on their higher incidence, then, proceed to analyze and determine the impact generated in you contribute. the interview, which consisted of a dialogue with the Director of Revenue Service Agency Chone on sanctions applied by the Tax Administration to taxpayers during 2014, after this, used the survey was conducted with a questionnaire closed to the population under study. Through the results it was identified that not required to keep accounting individuals were those that mostly failed to comply with its formal duties, and it was determined that the factor of greatest incidence is ignorance with 46%, it is concluded that the noncompliance with tax obligations caused a direct impact with business continuity, many have been financially penalized, closed, and even faced coercive actions, causing a decrease in tax revenues for the Ecuadorian state which is reflected with macros collection figures current.